2022
DOI: 10.1108/pm-09-2021-0064
|View full text |Cite
|
Sign up to set email alerts
|

Housing finance inaccessibility: evidence from the Nigerian Pensioners

Abstract: PurposeThe Nigerian Government’s initiatives to provide housing loans to low-income pensioners (LIPs) have been futile. This paper aims to examine the root cause of housing loan inaccessibility for the Nigerian LIPs and proffer some possible policy options. This is because inaccessibility to housing finance is one of the impediments facing the LIPs homeownership.Design/methodology/approachThe phenomenology type of qualitative research was employed to collate data. The study supports MAXQDA 2020 with thematic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…The study engaged six construction consultant experts from each location that have been directly or indirectly involved in the three case studies and two senior government officials from relevant ministries before saturation was achieved. To strengthen the study's reliability, the researchers tackle the restrictions of non-probability sampling methods such as researchers' biases, cost and time-effectiveness (Ebekozien et al, 2022). Fourteen interviewees from Abuja and Lagos were engaged.…”
Section: Methodsmentioning
confidence: 99%
“…The study engaged six construction consultant experts from each location that have been directly or indirectly involved in the three case studies and two senior government officials from relevant ministries before saturation was achieved. To strengthen the study's reliability, the researchers tackle the restrictions of non-probability sampling methods such as researchers' biases, cost and time-effectiveness (Ebekozien et al, 2022). Fourteen interviewees from Abuja and Lagos were engaged.…”
Section: Methodsmentioning
confidence: 99%
“…shows that demand and supply affect housing affordability in the study area. The previous study by Ebekozien et al (2022) shows that affordability in housing was largely affected by the demand and level of supply in the market. et al (2019), where the economic recession and level of corruption affected price control.…”
Section: Analysis Of Factors Affecting Residential Property Developmentmentioning
confidence: 96%
“…In addition to building expenditures, interest expenses are among a property developer's major expenses. Whether or whether the house was sold, interest on property loans must be capitalized and subtracted, just like other development expenditures (Ebekozien et al 2022).…”
Section: Purchasing Powermentioning
confidence: 99%
“…Accessing mortgages by urban LIE is challenging to buy homes in many developing countries, including Nigeria. In Nigeria, a few studies (Wapwera et al, 2011;Taiwo et al, 2017;Adegun and Olusoga, 2019;Ekpo, 2019;Dafeamekpor et al, 2022;Ebekozien et al, 2022) attempted to examine the relevance of self-help in housing provision, but rare from the perspective of improving sustainable urban resilience in low-income housing provision. Wapwera et al (2011) identified and analysed Nigeria's housing finance methods for the LIEs.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, a few studies (Wapwera et al ., 2011; Taiwo et al. , 2017; Adegun and Olusoga, 2019; Ekpo, 2019; Dafeamekpor et al ., 2022; Ebekozien et al ., 2022) attempted to examine the relevance of self-help in housing provision, but rare from the perspective of improving sustainable urban resilience in low-income housing provision. Wapwera et al .…”
Section: Introductionmentioning
confidence: 99%